2002
DOI: 10.1177/0022167802421004
|View full text |Cite
|
Sign up to set email alerts
|

Toward an Entheogen Research Agenda

Abstract: The word entheogen was coined to denote psychedelic chemicals and botanicals that engender the experience of god within. Drawing on William James, Charles Tart, and Ken Wilber, the authors claim that a complete study of religion must include entheogens, and they propose topics leading toward an entheogen research agenda:(a) the spiritual nature of the human mind, (b) the dispute over the authenticity of entheogen-assisted religious experiences, (c) pastoral counseling, (d) experimental mysticism, (e) entheogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
5
0
1
Order By: Relevance
“…With the lessening of fear and anxiety, feelings of love can come to the surface, allowing patients to examine their lives from a more secure place, which is one of the core reasons that MDMA is so effective in facilitating therapy (Greer & Tolbert, 1990; Mithoefer et al, 2011). For patients with terminal illnesses, the experience of love can be especially transformative (Grob et al, 2013; Roberts & Hruby, 2002). Bossis (2014), in recalling clinical studies using psilocybin with advanced-stage cancer, noted that patients reported experiences akin to what would be considered agape, or universal love.…”
Section: Present-day Research With Psychedelicsmentioning
confidence: 99%
See 1 more Smart Citation
“…With the lessening of fear and anxiety, feelings of love can come to the surface, allowing patients to examine their lives from a more secure place, which is one of the core reasons that MDMA is so effective in facilitating therapy (Greer & Tolbert, 1990; Mithoefer et al, 2011). For patients with terminal illnesses, the experience of love can be especially transformative (Grob et al, 2013; Roberts & Hruby, 2002). Bossis (2014), in recalling clinical studies using psilocybin with advanced-stage cancer, noted that patients reported experiences akin to what would be considered agape, or universal love.…”
Section: Present-day Research With Psychedelicsmentioning
confidence: 99%
“…While not a consensus, there is a vein in the limited discourse on therapist skills and training that suggests the need for psychedelic therapists to be versed in a meditation or contemplative practice (Pahnke, 1963; Richards, 2005; Strassman, 2010). Possibly they have experienced and integrated mystical states of awareness and have found the experience of value (Roberts & Hruby, 2002). Such experiences of alternate states can serve to help therapists embody the empathetic abiding presence called for in this work, as well as tolerance for moments in psychedelic sessions in which the participant is experiencing paradoxical, intense emotional and physical states.…”
Section: The Competencies Of the Therapist Guide For Psychedelic-assi...mentioning
confidence: 99%
“…Equally importantly to their potential for clinical applications, psychedelics open intriguing avenues for scientifically exploring humanistic, including trans-personal, phenomena that have eluded other methods (e.g., see Roberts & Hruby, 2002, who have outlined a proposed research agenda for psychedelics used as entheogens). Perhaps psychedelics could revitalize introspective approaches that characterized the earliest phase of experimental psychology?…”
Section: Psychedelics' Humanistic Research Implicationsmentioning
confidence: 99%
“…Studentima teološkog seminara dali su psilocibin (eksperimentalna skupina) i nikotin (kontrolna skupina). Rezultati su pokazali da unutar pravoga seta i settinga korištenje psihoaktivnih supstanci može dovesti do iskustva sličnog mističnom (Barušs 2003;Grinspoon i Bakalar 1979;Lerner i Lyves 2006;Roberts i Hruby 2002). Prema statističkim podacima, od četvrtine do trećine opće populacije imat će religijska iskustva prilikom uzimanja droga u prirodnim uvjetima; kod subjekata s izraženijom religijskom inklinacijom ta proporcija se penje do tri četvrtine, a ako se koristi u religijskom okruženju devet od deset ljudi ima takvo religijsko iskustvo (Smith 1964: 520).…”
Section: Povijesni Kontekst Upotrebe Psihoaktivnih Sredstavaunclassified